The Influence of Product Quality and Service Quality on Customer Satisfaction at Butterfields Café - Audreya, Qonita; Kurniawan, Johannes; Juliana, Juliana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The cafe industry has experienced significant growth in recent years, driven mainly by lifestyle changes and the increasing culture of coffee consumption in various countries. In this context, the quality of the products sold and the quality of service provided by the cafe are very important to encourage and improve customer satisfaction. The purpose of this study is to analyze the effect of product quality and service quality on customer satisfaction at Buterfields Café. This study is important to conduct because there is still a lack of research that combines these two variables. In this study, the researcher used a purposive sampling technique to determine the number of samples. The sample of this study consisted of 160 respondents who were customers who had made purchases in the last one month at least. Data were obtained through the distribution of questionnaires designed to measure the perceptions given by respondents regarding product quality and service quality provided. The data analysis technique used was Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of the analysis that have been found, show that product quality (β=0,492) makes an important contribution in building customer satisfaction through perceptions of taste and presentation, while service quality (β=0,391) plays a role in creating a positive experience for customers with an R² value indicating the strength of the model (64.6%). These findings indicate that Butterfields Café can improve its marketing strategy by focusing on improving product and service quality. Butterfields Café needs to continuously maintain and improve the quality of its products and services, for example by developing dishes based on local Bogor ingredients, using high-quality materials, implementing service recovery training programs or incentive systems based on customer reviews, addressing areas of improvement highlighted by customers, and adapting to customer preferences in order to enhance customer satisfaction.